COMPARATIVE ANALYSIS OF DEPOSIT BETWEEN BANK MEGA AND BANK MUAMALAT - I nyoman Budiono; Abdul Hamid; Andi Kiki Patmawati; Nur Ainun Herawati Samad; Andi Dinul Islam Firdaus (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2026)
This study analyzes the fundamental operational differences of deposit products between conventional banking (Bank Mega) and Islamic banking (Bank Muamalat). Using a qualitative descriptive method, the study reveals that basic principles affect accessibility and cost structures for customers. Significant differences were found in minimum requirements and penalty consequences. Bank Mega sets a minimum balance for both regular and online account openings. Withdrawals before maturity incur a 1% penalty of the nominal amount and forfeiture of accrued interest. In contrast, Bank Muamalat, which applies the Mudharabah Mutlaqah principle, offers higher accessibility with a lower minimum. Early withdrawal fees are also lighter, being only a fixed account closure fee. Overall comparison shows similarities in aspects such as account opening/closing media, deposit term options, and the automatic renewal system. However, the core difference lies in the operational principles; Bank Mega is based on interest-based principles, whereas Bank Muamalat strictly applies Sharia principles.